Metacognitive and social cognition training (MSCT) in schizophrenia: a preliminary efficacy study - Rocha, Nuno (2014)
Psychosocial interventions have proven to be effective in treating social cognition in people with psychotic disorders. The current study aimed to determine the effects of a metacognitive and social cognition training (MSCT) program, designed to both remediate deficits and correct biases in social cognition. Thirty-five clinically stable outpatients were recruited and assigned to the MSCT program (n = 19) for 10 weeks (18 sessions) or to the TAU group (n = 16), and they all completed pre- and post-treatment assessments of social cognition, cognitive biases, functioning and symptoms. The MSCT group demonstrated a significant improvement in theory of mind, social perception, emotion recognition and social functioning. Additionally, the tendency to jump to conclusions was significantly reduced among the MSCT group after training. There were no differential benefits regarding clinical symptoms except for one trend group effect for general psychopathology. The results support the efficacy of the MSCT format, but further development of the training program is required to increase the benefits related to attributional style.